Performance Analysis of An Arduino Based Calibration and Temperature Control System for A Refractance Window Dryer - Mutumba, Raymonds; Kigozi, Julia; Tumutegyereize, Peter; Ssenyimba, Shaffic; Muyonga, John (African Journal of Biotechnology, 2011)
Automated control of temperature in fruit dryers is important for product quality and retention of nutrient content. In this study, the continuous refractance window dryer (RWD) was calibrated for drying temperature to enable the dryer to be set to dry a wide range of products. The drying operation in a RWD is carried out over a bed of hot water. The calibration system comprised of a computer program, calibrated knob, arrangement of sensors and output components. A computer program was successfully written in Arduino environment and a circuit board connected. A DS18B20 sensor was used to read the hot water temperature and a 5V potentiometer employed to vary the voltage as it corresponds to the desired water temperature. The system calibration focused on drying temperatures for mango, tomato and pineapple, but it can be applied to any other food products since the optimum drying temperature for most food products falls within the considered range. A calibration equation relating potentiometer voltage and temperature was formulated with the potentiometer maximum angular sweep found to be 295°. This angular sweep corresponded with 94.9996°C as the maximum calibration temperature. The system was found to be 97.6% accurate at attaining the desired temperature. A calibrated label was developed and marked accordingly. The developed system was simple to operate and robust throughout the testing hence it can be recommended for similar machines.
Keywords: Automation; Calibration; Temperature; Refractance window dryer